School restrictions on outdoor activities and weight status in adolescent children after Japan's 2011 Fukushima Nuclear Power Plant disaster: a mid-term to long-term retrospective analysis. Issue 9 (28th September 2016) - Nomura, Shuhei; Blangiardo, Marta; Tsubokura, Masaharu; Ochi, Sae; Hodgson, Susan
Abstract : Objective: Radiation fears following Japan's 2011 Fukushima nuclear disaster affected levels of physical activity in local children. We assessed the postdisaster versus predisaster weight status in school children and evaluated to what extent school restrictions on outdoor activities that were intended to reduce radiation exposure risk affected child weight. Participants: We considered children aged 13–15 years from 4 of the 5 secondary schools in Soma City (n=1030, 99.1% of all children in the city), located in 35–50 km from the Fukushima nuclear plant, postdisaster (2012 and 2015) and predisaster (2010). Methods: Weight status, in terms of body mass index (BMI), percentage of overweight (POW) and incidence of obesity and underweight (defined as a POW ≥20% and ≤−20%, respectively) were examined and compared predisaster and postdisaster using regression models. We also constructed models to assess the impact of school restrictions on outdoor activity on weight status. Results: After adjustment for covariates, a slight decrease in mean BMI and POW was detected in females in 2012 (−0.37, 95% CI −0.68 to −0.06; and −1.97, 95% CI −3.57 to −0.36, respectively). For male children, obesity incidence increased in 2012 (OR for obesity: 1.45, 95% CI 1.02 to 2.08). Compared with predisaster weight status, no significant weight change was identified in 2015 in either males or females. School restrictions on outdoor activities were not significantly associated with weight status. Conclusions: 4 years following the disaster, weight status has recovered to the predisaster levels for males and females; however, a slight decrease in weight in females and a slight increase in risk of obesity were observed in males 1 year following the disaster. Our findings could be used to guide actions taken during the early phase of a radiological disaster to manage the postdisaster health risks in adolescent children.